PENGARUH PERMODALAN, RISIKO KREDIT, DAN RISIKO LIKUIDITAS TERHADAP PROFITABILITAS PADA BANK DENGAN KATEGORI BUKU (BANK UMUM KEGIATAN USAHA) - Antyo Pracoyo; Aulia Imani (Media Ekonomi, 2017)
This study aims to analyze the influence of bank specific components on the profitability of the banking industry with the category of Commercial Business Activities (BUKU) 3 in the period 2011-2015. The analytical method used is the analysis of Multiple Linear Regression with the number of samples of 8 banks or Foreign Exchange Banks in BOOK 3. The independent variables used for this study are based on bank ratios, capital measured by Capital Adequacy Ratio, Credit Risk measured by Non-Performing Loans, and Liquidity Risk is measured by Loan to Deposit Ratio. The dependent variable is Profitability measured by Return On Assets (ROA). The results of this study indicate that Capital Risk and Liquidity have no significant effect on profitability. Meanwhile, Credit Risk has a significant effect on Profitability